2022
DOI: 10.3390/ijms23115909
|View full text |Cite
|
Sign up to set email alerts
|

Response of Poplar and Associated Fungal Endophytic Communities to a PAH Contamination Gradient

Abstract: Microbial populations associated to poplar are well described in non-contaminated and metal-contaminated environments but more poorly in the context of polycyclic aromatic hydrocarbon (PAH) contamination. This study aimed to understand how a gradient of phenanthrene (PHE) contamination affects poplar growth and the fungal microbiome in both soil and plant endosphere (roots, stems and leaves). Plant growth and fitness parameters indicated that the growth of Populus canadensis was impaired when PHE concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…We showed in a previous study on the same samples (Gréau et al 2022) that fungal endophytic community structure was impacted in the roots. Therefore, different responses of fungal and bacterial endophytes to the phenanthrene contamination seem to occur.…”
Section: Endophytic Communities Are Preserved From the Contaminationmentioning
confidence: 75%
See 4 more Smart Citations
“…We showed in a previous study on the same samples (Gréau et al 2022) that fungal endophytic community structure was impacted in the roots. Therefore, different responses of fungal and bacterial endophytes to the phenanthrene contamination seem to occur.…”
Section: Endophytic Communities Are Preserved From the Contaminationmentioning
confidence: 75%
“…We hypothesised that soil microbial community and functions would be impacted by the contamination and since soil microbial communities are the first reservoir of endophytic communities (Gaiero et al 2013;Pascale et al 2020), it would lead to a community shift in roots as shown in the literature with petroleum, hydrocarbon or metal stresses (Tardif et al 2016;Iffis, St-Arnaud and Hijri 2017;Lumactud and Fulthorpe 2018;Syranidou et al 2018). In a previous study using the same experimental design (Gréau et al 2022), we showed that poplar absorbed PHE in its tissues, at concentrations proportional to initial soil concentrations (see also Supplementary Table S2) and that fungal community structure of both soil and roots shifted due to increasing PHE concentrations. We thus explored the response of the bacterial community in term of taxonomic and functional diversity.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations